Impact of global warming on the odour and ammonia emissions of livestock buildings used for fattening pigs. (November 2018) - Schauberger, Günther; Piringer, Martin; Mikovits, Christian; Zollitsch, Werner; Hörtenhuber, Stefan J.; Baumgartner, Johannes; Niebuhr, Knut; Anders, Ivonne; Andre, Konrad; Hennig-Pauka, Isabel; Schönhart, Martin
Abstract : Ammonia and odour are the most relevant pollutants emitted from livestock buildings used for monogastric animal production. Whereas odour can cause annoyance in the close vicinity of the source, emission of ammonia is a precursor for the formation of particulate matter and acidification on a regional scale. Because of clean air regulation in Europe, total ammonia emissions reduced by 23% between 1990 and 2015 whilst, over the same period, anthropogenic warming became more and more evident. By a simulation of the indoor climate of a confined livestock building with a mechanical ventilation for 1800 fattening pigs, the modification of the odour and ammonia emission was calculated for the period between 1981 and 2017. For ammonia emission, a relative increase of 0.16% per year was determined. But following the clean air endeavour between 1990 and 2015 emissions over that period were reduced by 23%. The global warming signal counteracting this reduction in the range of 4% during over this period, which means that the overall reduction for the ammonia emission was only 19%. For Austria with a global warming increase of 1% from 1990 to 2015, this gives an increase in emissions of 5% instead. Odour emissions also increased by about 0.16% per year. The relative increase of the separation distances for the four cardinal directions was about 0.06% per year, the related increase for the separation area was 0.13% per year. This case study on the fattening pigs shows that the global warming signal has a negligible impact on separation distances. Highlights: Odour and ammonia are relevant pollutants from monogastric animals. The modification of the indoor climate due to global warming is considered. An increase of 0.16%/a of NH3 emission was determine for confined livestock. The increase of NH3 emission counteract the clean air efforts. No significant impact on the separation distances for odour was found.